EQUIPMENT STANDARDIZATION IN ORDER TO IMPLEMENT OCCUPATIONAL HEALTH AND SAFETY STANDARDS IN CONSTRUCTION WORK REVIEWED FROM LAW NUMBER 2 OF 2017 CONCERNING CONSTRUCTION SERVICES, LAW NUMBER 13 OF 2003 CONCERNING EMPLOYMENT AND FIDIC - Sheehan Ariel Mohammed Gaffar; Purnama Trisnamansyah; Holyness N Singadimedja (RADJA PUBLIKA, 2025)
The implementation of equipment standardization and occupational health and safety (OHS) in construction projects in Indonesia is regulated through several laws and regulations and refers to international guidelines such as ILO Convention No. 155 of 1981 concerning Occupational Health and Safety and FIDIC. Although these regulations require compliance with technical, safety, and occupational health standards, their implementation still experiences various obstacles. This can be seen from the continued use of obsolete and uncertified equipment, as well as the high number of work accidents. To improve the effectiveness of standardization, the supervision and law enforcement system in Indonesia can be compared with other countries such as the Philippines. Therefore, reform efforts are needed in supervision, enforcement of sanctions, and increased education to increase awareness and compliance with OHS standards, so as to protect workers and create a safe and sustainable work environment.